2017
DOI: 10.1515/orga-2017-0001
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Expatriation Process in a Slovenian Company

Abstract: Background and Purpose: The multinational companies require different approach of human resource management to achieve their goals. The reason is in employees who are working abroad, so-called expatriates. The purpose of the research is to investigate perceptions and experience of the expatriates working in one of the Slovenian multinational company.Design/Methodology/Approach: The online survey was performed among all expatriates working for the pharmaceutical company. The questionnaire was randomly sent and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0
6

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 50 publications
0
8
0
6
Order By: Relevance
“…It is similar to expatriates in Kurdistan (Hamze, 2020) and Malaysia (Ramlan et al, 2018). Slovenia does not report on expatriates' issues (Pintar et al, 2017). However, Gudmundsdottir (2015) found that motivation facilitates expatriates working performance among Nordic expatriates in the United States.…”
Section: Introductionmentioning
confidence: 77%
“…It is similar to expatriates in Kurdistan (Hamze, 2020) and Malaysia (Ramlan et al, 2018). Slovenia does not report on expatriates' issues (Pintar et al, 2017). However, Gudmundsdottir (2015) found that motivation facilitates expatriates working performance among Nordic expatriates in the United States.…”
Section: Introductionmentioning
confidence: 77%
“…A expatriação compreende práticas como recrutamento e seleção; preparação e adaptação da família; treinamento técnico e cultural; fornecimento de documentos a todos os envolvidos; gestão de desempenho, carreira e conhecimento; remuneração; suporte psicológico (FLYNN, 1995;DUNBAR;ODDOU, 1987;ODDOU et al, 2009;SCHEFFER;BITENCOURT, 2013;KNOCKE;SCHUSTER, 2017;TUNG, 2016;PINTAR;MARTINS;BERNIK, 2017;SUUTARI et al, 2018;CHIANG et al, 2018;TAHIR;EGLESTON, 2019). Essas variáveis conectam-se ao sucesso da missão (FLYNN, 1995).…”
Section: Expatriaçãounclassified
“…A expatriação propicia vantagens tanto para a empresa quanto para o empregado (CHIANG et al, 2018): para a organizaçãodesenvolvimento de liderança; expansão do mercado; solução de problemas; desenvolvimento da empresa (ODDOU et al, 2009) e para o empregadorealização profissional, pois implantar um projeto internacional é um grande desafio; exposição de sua capacidade e qualificação. (GALLON; SCHEFFER; BITENCOURT, 2013;PINTAR;MARTINS;BERNIK, 2017). O empregado, ao aceitar a expatriação, sente-se mais valorizado pela empresa e, por consequência, tende a se comprometer mais.…”
Section: Expatriaçãounclassified
“…Only the article by Pinto et al (2012) reveals that expatriation was initiated by the company and required commitment from the assignee, which indicates that in this particular case, different options to expatriate were not evaluated prior to expatriation. Four articles studying financial professionals, engineers, designers, lawyers, senior care assistants, and government officials demonstrate that individuals expatriate as AEs for career reasons; however, these articles do not discuss whether individuals evaluate options to expatriate as SIEs (e.g., Cuhlova, 2017;Martins and Bernik, 2017;Shortland, 2018). Only one article of the four (e.g., Doherty et al, 2011) indicates that individuals moved as SIEs.…”
Section: Findings Careermentioning
confidence: 99%
“…In this case, career progression expectations refer to expectations of finding new work responsibilities and new professional challenges while working abroad ( Dickmann and Mills, 2010 ; Farcas and Goncalves, 2017 ). In a similar vein, financial professionals, engineers, designers, lawyers, senior care assistants, and government officials are discussed in four articles, in which it is argued that they expect to meet their career progression expectations if they move abroad (e.g., Doherty et al, 2011 ; Cuhlova, 2017 ; Shortland, 2018 ) or to upgrade their knowledge and improve their general skills ( Martins and Bernik, 2017 ).…”
Section: Introductionmentioning
confidence: 99%